Analisis pembiayaan mikro UMKM dengan akad musyarakah mutanaqisah pada Bank Syariah Indonesia KCP Trunojoyo Bangkalan - Syaifullah, Muhammad Ilham (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2024)
This study was conducted with the aim of analyzing micro financing of MSMEs with the Musyarakah Mutanaqisah contract at Bank Syariah Indonesia, Trunojoyo Branch Office, Bangkalan. The research method used in this study is a qualitative descriptive method. Data collection techniques were carried out by observation and interviews. Based on the results of the study, it shows that in micro financing of MSMEs with the Musyarakah Mutanaqisah contract at Bank Syariah Indonesia, Trunojoyo Branch Office, Bangkalan through an agreement between the customer and the bank with an agreement on the assets or goods needed by the customer first, then the bank will conduct a field survey to the customer which will then be disbursed according to the approval of the head of the bank. It can be concluded that micro financing of MSMEs using the Musyarakah Mutanaqisah contract is a financing process for small and medium micro businesses through a financing agreement with a capital cooperation scheme for the purchase of goods or property in asset ownership with applicable sharia provisions.